Manajemen Pondok Pesantren dalam Meningkatkan Kompetensi Santri di Madrasah Bertaraf Internasional Amanatul Ummah Pacet Mojokerto - Mokhamad Syaiful Faris (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The results of the research show that 1) Islamic boarding school management planning in improving the competency of students, namely starting from the planning, implementation and management evaluation stages which started from the beginning of the year activities to the end of year activities, namely teacher work meeting activities which included all the elements in MBI Amanatul The ummah of functionary teachers, security guards, sweepers and so on are involved. 2) Implementation of Islamic Boarding Schools in improving the competency of santri, there are daily programs, various extracurricular and organizational activities are handled seriously so that many santri graduates become leaders at universities (such as the President of BEM, head of UKM) and there are reminders of the 7 keys to success that are always upheld. 3) Obstacles and solutions in improving the competency of students, namely the presence of teachers and asatidz, not all of whom live in Islamic boarding schools or in the surrounding area. The solution provided by the institution is the existence of adequate transportation facilities to pick up and pick up teachers and their Asatidz.